Structure of epitaxial SrIrO3 perovskite studied by interference between X‐ray waves diffracted by the substrate and the thin film. Issue 2 (28th February 2017) - Horák, Lukáš; Kriegner, Dominik; Liu, Jian; Frontera, Carlos; Marti, Xavier; Holý, Václav
Abstract : The unit‐cell parameters of metastable orthorhombic SrIrO3 phases epitaxially stabilized on various substrates (DyScO3, GdScO3, NdScO3 and SrTiO3 ) are reported. The atomic coordinates of the SrIrO3 layers are determined by collecting X‐ray diffraction curves of a large number of Bragg peaks. The present method, which is described in detail, utilizes not only the Bragg peak intensities but also the interference between waves diffracted by the substrate and the thin film. Abstract : A high‐pressure metastable orthorhombic phase of SrIrO3 perovskite has been epitaxially stabilized on several substrates (DyScO3, GdScO3, NdScO3 and SrTiO3 ) in the form of thin monocrystalline layers with (110) surface orientation. The unit‐cell parameters of the pseudomorphic thin SrIrO3 layers depend on the biaxial strain imposed by the various substrates due to the different lattice mismatches of the particular substrate and the bulk orthorhombic SrIrO3 structure. Using X‐ray diffractometry, it is shown that both compressive and tensile strain increase the lattice parameters a and b, while the angle γ scales with the applied strain, being smaller or larger than 90° for compressive or tensile strain, respectively, resulting in a small monoclinic distortion of the layer unit cell. Owing to the similarity of the substrate and layer lattices, the diffraction signals from the two structures overlap partially, which complicates structure determination by standard refinement methods using measured integrated intensities. The measured signal is composed of two interfering components corresponding to the waves diffracted by the substrate and by the layer, where the first component is calculated exactly using the known substrate structure, while the second one is determined by the unknown unit‐cell parameters of the layer. The unit‐cell parameters were refined in order to fit the experimental data with the simulation. The fractional coordinates of the atoms in the unit cell resulting from the fit are similar to those in the bulk structure.